Microarray analysis of the genomic effect of eugenol on methicillin-resistant Staphylococcus aureus - Buru, Ayuba Sunday; Neela, Vasantha Kumari; Mohandas, Kavitha; Pichika, Mallikarjuna Rao (Multidisciplinary Digital Publishing Institute, 2022)
Staphylococcus aureus is a highly adaptive human pathogen responsible for serious hospital- and community-acquired infectious diseases, ranging from skin and soft tissue infections, to complicated and life-threatening conditions such as endocarditis and toxic shock syndrome (TSS). The rapid development of resistance of this organism to available antibiotics over the last few decades has necessitated a constant search for more efficacious antibacterial agents. Eugenol (4-allyl-2-methoxyphenol) belongs to the class of chemical compounds called phenylpropanoids. It is a pure-to-pale yellow, oily liquid substance, mostly extracted as an essential oil from natural products such as clove, cinnamon, nutmeg, basil, and bay leaf. Eugenol has previously been shown to have antimicrobial activity against methicillin-resistant Staphylococcus aureus (MRSA). However, the mechanism of action of eugenol against MRSA has not, as yet, been elucidated; hence, the necessity of this study. Global gene expression patterns in response to challenge from subinhibitory concentrations of eugenol were analysed using the Agilent DNA microarray system to identify genes that can be used as drug targets—most importantly, essential genes involved in unique metabolic pathways elicited for bacterial survival. Transcriptomic analysis of fluctuating genes revealed those involved in amino acid metabolism, fatty acid metabolism, translational, and ribosomal pathways. In amino acid metabolism, for instance, the argC gene encodes for N-acetyl-gamma-glutamyl-phosphate reductase. The argC gene plays an important role in the biosynthesis of arginine from glutamate in the amino acid metabolic pathway. It is the enzyme that catalyses the third step in the latter reaction, and without this process the production of N-acetylglutamate 5-semialdehyde cannot be completed from the NADP-dependent reduction of N-acetyl-5-glutamyl phosphate, which is essential for the survival of some microorganisms and plants. This study enables us to examine complete global transcriptomic responses in MRSA when challenged with eugenol. It reveals novel information with the potential to further benefit the exploratory quest for novel targets against this pathogen, with a view to the development of efficacious antimicrobial agents for the treatment of associated infections.